2017
DOI: 10.1016/j.neuropsychologia.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the neural substrates of misinformation processing

Abstract: Word count abstract: 168Word count manuscript (excluding references, tables, and figure captions): 5350 1: AbstractIt is well known that information that is initially thought to be correct but then revealed to be false, often continues to influence human judgement and decision making despite people being aware of the retraction. Yet little research has examined the underlying neural substrates of this phenomenon, which is known as the 'continued influence effect of misinformation' (CIEM). It remains unclear h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 55 publications
0
36
1
1
Order By: Relevance
“…Unexpectedly, contrary to prior reports in the literature (e.g., Gordon et al, 2017), neither of our two studies found systematic neural processing differences during the encoding of correcting information in support of the model-updating account of the CIEM. Yet these null findings should be tentatively received.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, contrary to prior reports in the literature (e.g., Gordon et al, 2017), neither of our two studies found systematic neural processing differences during the encoding of correcting information in support of the model-updating account of the CIEM. Yet these null findings should be tentatively received.…”
Section: Discussioncontrasting
confidence: 99%
“…Unfortunately, traditional psychological measures struggle to disentangle these two stages of information processing as the CIEM's only behavioural indicator is people's level of reliance on misinformationa measure that inherently conflates the impact of encoding-and retrievalrelated processes. As a consequence, in their search for alternative means of inquiry, CIEM scientists have recently turned their attention towards neuroimaging techniques (e.g., Edelson et al, 2014;Gordon et al, 2017;Kaplan et al, 2016). Such techniques promise to be particularly relevant to the field given that they can monitor brain activity during different stages of information processing.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that WM capacity uniquely predicted susceptibility to the CIE suggests that the CIE may arise, at least partly, from a failure of integration, manipulation, and updating processes in WM, when the retraction is processed (Ecker et al, 2017;Gordon et al, 2017;Kendeou et al, 2014). Limited WM capacity will limit a person's ability to concurrently activate and integrate conflicting pieces of information, and then update and revise the corresponding event model accordingly.…”
Section: Discussionmentioning
confidence: 90%
“…In other words, to the extent that processing of the retraction does not result in immediate, adequate updating and revision of the initial, incorrect event model, later reasoning may rely unduly on corrected misinformation. A recent neuroimaging study lends some support to this notion, as the CIE was associated with failure of integration and coherence-building mechanisms mediated by the medial parietal and dorsolateral pre-frontal cortex (Gordon, Brooks, Quadflieg, Ecker, & Lewandowsky, 2017).…”
Section: Predictors Of the Ciementioning
confidence: 89%
“…Maintaining coherence thus requires effortful integration of new explanatory information into a revised mental model. Continued influence of the original information can occur if this integrative revision fails (Gordon, Brooks, Quadflieg, Ecker, & Lewandowsky, ; Kendeou, Walsh, Smith, & O'Brien, ). Integration is facilitated if readers are supplied with an alternative causal explanation that can serve to replace the misinformation in the mental model.…”
Section: Explanations For the Continued Influence Of (Mis)informationmentioning
confidence: 99%